One‐Pot and Gram‐Scale Synthesis of Fe‐Based Nanozymes with Tunable O2 Activation Pathway and Specificity Between Associated Enzymatic Reactions - Qiu, Yuwei; Cheng, Tianqi; Yuan, Bo; Yip, Tsz Yeung; Zhao, Chao; Lee, Jung‐Hoon; Chou, Shang‐Wei; Chen, Jian Lin; Zhao, Yufei; Peng, Yung‐Kang (Small (Weinheim an der Bergstrasse, Germany), 2025)
Nanozymes have recently gained attention for their low cost and high stability. However, unlike natural enzymes, they often exhibit multiple enzyme‐like activities, complicating their use in selective bioassays. Since H2O2 and O2 are common substrates in these reactions, controlling their activation—and thus reaction specificity—is crucial. Recent advances in tuning the chemical state of cerium have enabled control over H2O2 activation pathways for tunable peroxidase/haloperoxidase‐like activities. In contrast, the control of O2 activation on an element in oxidase/laccase nanozymes and the impact of its chemical state on these activities remains unexplored. Herein, a facile one‐pot method is presented for the gram‐scale synthesis of Fe‐based nanozymes with tunable compositions of Fe3O4 and Fe3C by adjusting preparation temperatures. The Fe3O4‐containing samples exhibit superior laccase‐like activity, while the Fe3C‐containing counterparts demonstrate better oxidase‐like activity. This divergent O2 activation behavior is linked to their surface Fe species: the abundant reactive Fe2+ in Fe3O4 promotes laccase‐like activity via Fe3+‐superoxo formation, whereas metallic Fe in Fe3C facilitates OH radical generation for oxidase‐like activity. Controlled O2 activation pathways in these Fe‐based nanozymes demonstrate improved sensitivity in the corresponding biomolecule detection, which should inform the design of nanozymes with enhanced activity and specificity. Regulating the reaction specificity of nanozymes is a challenging task. Herein, one‐step mass production of Fe‐based nanozymes containing either Fe3O4 or Fe3C is presented, which can be used directly without purification. These nanozymes activate O2 via different pathways and hence exhibit distinct reaction specificity in oxidase‐ and laccase‐like activities, enabling the selective detection of biomolecules.